1998
DOI: 10.1017/s0967199498000057
|View full text |Cite
|
Sign up to set email alerts
|

Impaired development of zygotes with uneven pronuclear size

Abstract: The correlation between human zygote morphology and chromosomal anomalies after cleavage has not been well characterised. Commonly observed morphological qualities at the zygote stage have provided little insight into further development, and therefore selection for cryopreservation or transfer appears to be less specific than that at later stages of preimplantation development. The purpose of this work was to evaluate the relationship between aberrant pronuclear morphology and chromosomal anomalies after clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 19 publications
3
34
1
5
Order By: Relevance
“…In our results from group Z4, the association between asymmetric and/or separate PNs and poor prognosis embryos was confirmed [5]. Pronuclear morphology studies have found that differences of more than 4 µm in the diameter of PNs are associated with aneuploidy [6]. The analysis of chromosomal status of embryos from different patterns suggests a lower incidence of chromosomal abnormalities in patients aged < 37 years with zygotes with similar PN size [31].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In our results from group Z4, the association between asymmetric and/or separate PNs and poor prognosis embryos was confirmed [5]. Pronuclear morphology studies have found that differences of more than 4 µm in the diameter of PNs are associated with aneuploidy [6]. The analysis of chromosomal status of embryos from different patterns suggests a lower incidence of chromosomal abnormalities in patients aged < 37 years with zygotes with similar PN size [31].…”
Section: Discussionsupporting
confidence: 74%
“…Multinucleation is present in the same proportion in embryos for each PN pattern both in our data and in Tesarik's. We find poor prognosis embryos from pattern 4 zygotes, with a higher percentage of blastomere multinucleation compared to the data from Tesarik and Greco [4] and Sadowy et al [6]. It would seem that the presence of a very low number of NPBs (corresponding to p4) in any PN is a poor prognosis factor for embryo development.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The PN-like body was then absorbed into the ooplasm and migrated toward the mPN, leading to formation of an uneven 2PN embryo ( Figure 5). Although it has been reported that zygotes with uneven 2PN may correlate with ooplasmic immaturity and chromosomal abnormalities [22,23], the etiology and physiological significance of those zygotes are still unknown. The TLC analyses in this study demonstrated for the first time a possible mechanism for the formation of uneven 2PN zygotes.…”
Section: Translucent Zone In Peripheral Ooplasm (Cytoplasmic Halo) (Smentioning
confidence: 99%
“…This is usually achieved either by the extended culture of human embryos to the blastocyst stage [5,6] or by the morphological analysis and selection of the highest quality embryos for transfer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, the assessment of zygote quality has been applied [23][24][25][26][27][28][29][30][31][32]. Although these techniques have greatly assisted in achieving an acceptable pregnancy rate with the minimum number of embryos transferred into the uterus, one aspect of these protocols is that non-transferred embryos are discarded or cryopreserved.…”
Section: Introductionmentioning
confidence: 99%